Determining the need for repeat testing of blood ethanol concentration: Evaluation of the synchron blood ethyl alcohol assay kit - Ustundag Yasemin; Huysal Kağan; Eşmedere-Eren Sevim (Journal of Medical Biochemistry, 2019)
Background: In clinical laboratories, a common practice used to verify tests prior to reporting is repeat testing. Our objective was to evaluate the differences between the results of blood ethanol concentration (BEC) test repetitions and report on the role of repeat testing to prevent reporting of incorrect results. Methods: We conducted a retrospective study of data retrieved from the Bursa Yuksek Ihtisas Training and Research Hospital's document management system by calculating the percentage change between repeated BEC test runs. To assess for clinical relevance, the bias between two results from the same sample was compared using the 1988 Clinical Laboratory Improvement Amendments' (CLIA) proficiency testing allowable total error (TEa) limits. Results: From a total of 1,627 BEC tests performed between January 2017 and January 2018, 70% (1,133) were repeat tested. Of these, 830 resulted in BECs between 0-5 mmol/L, of which 237 (28.5%) were above the 25% acceptable TEa. Two hundred seventy-six BEC test results were greater than >14 mmol/L, and there was a good consensus between the initial and repeat test results (99%). In this group, the mean bias was 0.0% (95%, CI = -9.8-9.8% ). However, three of the repeat test results were considered significantly different. There were two discordant results in the 5-14 mmol/L ethanol level, and the mean bias was 2.1% (95%, CI = -15.0-19.1% ). Conclusions: The majority of the repeated BEC test values were the same as the baseline value; therefore, there may be limited benefit in continuing such frequent repeated analyses.